2022
DOI: 10.3389/fneur.2022.857133
|View full text |Cite
|
Sign up to set email alerts
|

Elevated red cell distribution width predicts residual dizziness in patients with benign paroxysmal positional vertigo

Abstract: ObjectiveThe present study aimed to determine whether residual dizziness (RD) after successful repositioning treatment in benign paroxysmal positional vertigo (BPPV) patients could be predicted by red blood cell distribution width (RDW).Materials and methodsIn this study, a total of 303 BBPV patients hospitalized at the neurology department were investigated. The enrolled patients were divided into two groups after successful repositioning treatment: non-RD group included patients who were completely cured, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…There is evidence that BPPV patients have higher levels of oxidative stress than healthy groups. Oxidative stress is a critical factor in microcirculation disturbances through the induction of erythrocyte adhesion to the vascular endothelium and the reduction of erythrocyte deformability (20). It has also been suggested that oxidative stress might play a role in the development of BPPV through its relationship with calcium metabolism and the direct toxic effects of free oxygen radicals, including the triggering of apoptosis (21).…”
Section: Pathophysiology Of Bppvmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that BPPV patients have higher levels of oxidative stress than healthy groups. Oxidative stress is a critical factor in microcirculation disturbances through the induction of erythrocyte adhesion to the vascular endothelium and the reduction of erythrocyte deformability (20). It has also been suggested that oxidative stress might play a role in the development of BPPV through its relationship with calcium metabolism and the direct toxic effects of free oxygen radicals, including the triggering of apoptosis (21).…”
Section: Pathophysiology Of Bppvmentioning
confidence: 99%
“…Otolin-1 is considered an inner ear-specific glycoprotein that can pass the blood-labyrinth barrier and be detected in peripheral blood (124). Elevated RDW is a potential rapid, inexpensive, and readily available laboratory biomarker of RD (20). Elevated RDW promotes platelet activation and aggregation and is a marker of the procoagulant status of red blood cells.…”
Section: Emerging Therapies and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation